2016
DOI: 10.17268/sci.agropecu.2016.03.22
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds with antioxidant capacity of the native Andean potato (Solanum tuberosum L.) Huagalina variety in La Libertad- Peru

Abstract: Potato is grown and consumed throughout the world for their particular calorific nutritional value and vitamin C, but it also contains phytochemicals (secondary metabolites) that have been studied and found to have positive effects in preventing degenerative diseases in human health, such as hypertensive activity, and also atherosclerosis, type 2 diabetes, liver fibrosis, Alzheimer's disease, macular degeneration and cancer. We aimed to identify and quantify phenolic compounds in potatoes grown on El Zuro (EZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…From our data, coumaric acid and chlorogenic acid were major phenols identified in potato tubers. This in part seems to correspond with the results of Rojas‐Padilla and Vásquez‐Villalobos who found that chlorogenic acid is the major phenol in Andean potato tubers. In spite of the several health benefits of phenolics, they act as important antioxidants under environmental stresses, regulate reactive oxygen species (ROS) level and protect plants against oxidative stress, thereby, the biosynthesis of phenols increases in response to salinity .…”
Section: Discussionsupporting
confidence: 90%
“…From our data, coumaric acid and chlorogenic acid were major phenols identified in potato tubers. This in part seems to correspond with the results of Rojas‐Padilla and Vásquez‐Villalobos who found that chlorogenic acid is the major phenol in Andean potato tubers. In spite of the several health benefits of phenolics, they act as important antioxidants under environmental stresses, regulate reactive oxygen species (ROS) level and protect plants against oxidative stress, thereby, the biosynthesis of phenols increases in response to salinity .…”
Section: Discussionsupporting
confidence: 90%
“…However, further research is required to identify any other substances that can be harmful to health depending on the amount consumed. The thirteen metabolites found in potato cooking water are the same as those found in raw potatoes of the same variety and origin (Rojas-Padilla & Vasquez-Villalobos, 2016).…”
Section: Resultssupporting
confidence: 53%
“…(2019). Moreover, Rojas‐Padilla and Vásquez‐Villalobos (2016) traced ferulaldehyde in potato but with lower concentration. Curcumin (compound 20) was discovered only in the light‐roasted coffee beans in the negative mode with [M−H] − ion m/z at 367.1187.…”
Section: Resultsmentioning
confidence: 99%